1985
DOI: 10.1207/s15326888chc1401_2
|View full text |Cite
|
Sign up to set email alerts
|

Role Perception of Mothers Who Have Hospitalized Children

Abstract: Childhood illness and hospitalization are stressful events for a family. Minimizing the trauma of hospitalization for children and their parents is a goal for health care workers in pediatric settings. This study examined the way in which mothers perceive their role in caring for their hospitalized children. Communication between the nurse and mother concerning that role was also explored. Results showed that the majority of mothers prefer to perform many child-care activities for their hospitalized children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 3 publications
5
19
0
Order By: Relevance
“…Webb et al(1985) found that 43% of parents either did or felt they could do a dressing change, while Hill identified that 38% of mothers wanted to do this care. The proportion of parents who were willing to give oral medication ranged from 60% in Algren's (1985)study to 89% in Hill's study. Kristensson-Hallstrom and Elander, and Webb et al reported that overall, parents believed that they could have provided more care than they actually did provide.…”
Section: Parents' Care Activitiesmentioning
confidence: 87%
See 4 more Smart Citations
“…Webb et al(1985) found that 43% of parents either did or felt they could do a dressing change, while Hill identified that 38% of mothers wanted to do this care. The proportion of parents who were willing to give oral medication ranged from 60% in Algren's (1985)study to 89% in Hill's study. Kristensson-Hallstrom and Elander, and Webb et al reported that overall, parents believed that they could have provided more care than they actually did provide.…”
Section: Parents' Care Activitiesmentioning
confidence: 87%
“…Several researchers have used checklists of child care activities to identify activities parents participate in or in which they would like to participate (Algren, 1985;Blower, & Morgan, 2000;Hill, 1978;Jackson, Bradham, & Burwell, 1978;Kristensson-Hallstrom, & Elander, 1994;Merrow, & Johnson, 1968;Webb, Hull, & Madeley, 1985).…”
Section: Parents' Care Activitiesmentioning
confidence: 99%
See 3 more Smart Citations